Isolation and culture of motor neurons from the newborn mouse spinal cord. - Anderson, K; Potter, A; Piccenna, L; Quah, A; Davies, K; Cheema, S (2004)
A protocol for the isolation and culture of motor neurons from postnatal day 1 mouse spinal cord is described. After 72 h in culture, phase contrast microscopy reveals healthy cells with motor neuronal morphology and extensive neuritic processes. These neurons express the 75-kDa low-affinity neurotrophin receptor (p75NTR) and choline acetyltransferase (ChAT), both proteins are specifically expressed by neonatal and embryonic motor neurons in vivo. This protocol can be adapted for various postnatal motor neuron assays.